Body image and body (dis)satisfaction in adolescence: differences between adolescent boys and girls - Erceg, Inja (Array, 2014)
Body image is a subjective representation of one’s physical appearance that reflects perceptions, opinions and feelings connected to one’s body. Body dissatisfaction can be defined as a discrepancy between the ideal and the current body size and is a strong risk factor for eating disorders and excessive preoccupation with body and appearance. The aim of this study was to determine differences between adolescent boys and girls in their body image, body dissatisfaction, body image importance and various body change strategies. 532 high school students aged 16 to 19 (M=17.54, SD=.629 ; 55% females) filled in the Body Image and Body Change Questionnaire (McCabe & Ricciardelli, 2001) and answered to questions related to their body weight and height. The Body mass index (BMI) was significantly lower in girls (M=20.8) than in boys (M=22.7). BMI lower than 18.5, what is considered underweight, had 16% of girls and 5% of boys, whereas BMI higher than 25, what is considered overweight, had 5.4% of girls and 15.3% of boys. The higher the BMI in girls was, their satisfaction with body weight, shape and overall appearance was lower. No such correlation was observed among boys. Expectedly, results show that adolescent boys are more satisfied with their bodies in general, as well as with their body weight and shape, muscle tone and size and overall body appearance. They also give more importance to their body height, muscle tone and size than do girls. Concerning body change strategies, adolescent boys practice more strategies to increase their body weight, muscle tone and size in contrast to adolescent girls who practice more strategies to lose weight.